The Impact of PBL-ESD-Based Electronic Student Worksheets on Developing Scientific Argumentation Skills among Pre-Service Chemistry Teachers - Putri, Tiara Swastika; Rohaeti, Eli (Journal of Educational Sciences, 2025)
This study investigates the impact of using Electronic Student Worksheets (E-LKM) based on Problem-Based Learning (PBL) and Education for Sustainable Development (ESD) on enhancing the scientific argumentation skills of prospective chemistry teachers. The research was motivated by the observed low levels of scientific argumentation among chemistry education students, which are attributed to the lack of contextual and student-centered learning approaches that support 21st-century skills. The study employed a quasi-experimental method with a pretest-posttest control group design, involving two classes selected through cluster random sampling. The experimental group used PBL-ESD-based E-LKM, while the control group used conventional methods. Argumentation skills were measured using essay tests, and data were analyzed using N-Gain and independent sample t-tests. The results showed that the experimental class achieved a higher N-Gain score (0.662) compared to the control class (0.544), with both in the moderate category. The t-test indicated a significant difference between the two groups (sig. = 0.000 < 0.05). These findings demonstrate that integrating PBL and ESD in E-LKM is effective in improving students’ scientific argumentation skills and fostering critical thinking and sustainability awareness in chemistry education.